THE EFFECT OF HEALTH EDUCATION ON THE KNOWLEDGE AND ATTITUDES OF ADOLESCENT GIRLS REGARDING BREAST SELF-EXAMINATION - Aryani, Iin; Murbiah; Miskiyah Tamar (Jurnal Keperawatan Sriwijaya, 2026)
Aim: To determine the influence of health education on the knowledge and attitudes of adolescent girls regarding BSE at SMP Negeri 2 Palembang Method: This research is a quantitative study with a pre-experimental design using a one-group pre-test post-test approach. The instruments used were knowledge questionnaires (20 questions) and attitudes (16 questions), which were tested for validity and reliability. The study was conducted from April 17-19, 2024, with a sample of 38 ninth-grade female students selected using a purposive sampling technique. Data analysis was performed using a paired sample t-test. Result: The average knowledge score increased from 54.87 to 86.05, with a difference of 31.18, while the average attitude score increased from 69.50 to 87.68, with a difference of 18.18. The statistical test results showed a p-value of 0.000, indicating a significant difference before and after the intervention. Conclusion: Health education has an effect on the knowledge and attitudes of adolescent girls regarding breast self-examination at SMP Negeri 2 Palembang